Protection Against Umrah Fraud Based on the Civil Code - Maini, Mahrum; Lubis, Muhammad Ridwan (Universitas Islam Negeri Sumatera Utara, 2025)
Fraud cases in the organization of the Umrah pilgrimage are increasingly prevalent in Indonesia, causing significant losses for prospective pilgrims. Lack of public understanding of their legal rights and weak oversight of Umrah travel agencies are the main factors fueling this problem. This study aims to analyze the legal protection provided to victims of Umrah fraud under the Civil Code (KUHPerdata) and to examine the civil liability mechanisms applicable to perpetrators. The research method used is normative juridical, with a statutory approach and case studies. Data were obtained through literature review and documentation of relevant court decisions. Problem analysis was conducted by combining legal materials (secondary data) with primary data obtained in the field. In conclusion, the Civil Code provides a sufficient legal basis for protecting victims of Umrah fraud, both through default mechanisms and unlawful acts. Strengthening specific regulations and increasing legal education for the public is needed to prevent similar cases in the future.